2010
DOI: 10.1111/j.1365-2966.2010.16644.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep 1.1 mm-wavelength imaging of the GOODS-S field by AzTEC/ASTE - I. Source catalogue and number counts

Abstract: We present the first results from a confusion‐limited map of the Great Observatories Origins Deep Survey‐South (GOODS‐S) taken with the AzTEC camera on the Atacama Submillimeter Telescope Experiment. We imaged a field to a 1σ depth of 0.48–0.73  mJy beam−1, making this one of the deepest blank‐field surveys at mm‐wavelengths ever achieved. Although by traditional standards our GOODS‐S map is extremely confused due to a sea of faint underlying sources, we demonstrate through simulations that our source identi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…There are also five sources out of 122 (4%) followed up by the ALESS survey with ALMA (da Cunha et al 2015) with estimated stellar masses <10 9.75 M e which nevertheless show moderately high IR luminosities of ∼10 10.5 to ∼10 11.6 L e . Likewise, seven sources out of the 48 sources (15%) from the AzTEC/ASTE survey (Scott et al 2010), also identified based on their IR properties, have stellar masses below 10 9.75 M e . Additionally, from the Capak et al (2015) sample of ∼10 z = 5-6 galaxies, there is one source (HZ4) below our 10 9.75 M e threshold (stellar mass of  10 9.67 0.21 M e ), which nonetheless has a moderately high IR luminosity (10 11.13 L e ).…”
Section: Do Examples Of Low-mass But Ir-luminous  Z 2 Galaxies Exist?mentioning
confidence: 99%
“…There are also five sources out of 122 (4%) followed up by the ALESS survey with ALMA (da Cunha et al 2015) with estimated stellar masses <10 9.75 M e which nevertheless show moderately high IR luminosities of ∼10 10.5 to ∼10 11.6 L e . Likewise, seven sources out of the 48 sources (15%) from the AzTEC/ASTE survey (Scott et al 2010), also identified based on their IR properties, have stellar masses below 10 9.75 M e . Additionally, from the Capak et al (2015) sample of ∼10 z = 5-6 galaxies, there is one source (HZ4) below our 10 9.75 M e threshold (stellar mass of  10 9.67 0.21 M e ), which nonetheless has a moderately high IR luminosity (10 11.13 L e ).…”
Section: Do Examples Of Low-mass But Ir-luminous  Z 2 Galaxies Exist?mentioning
confidence: 99%
“…Even with the limited capabilities offered in Cycle 0, it has the resolution and sensitivity necessary to double the total number of interferometrically observed submillimeter sources in a matter of hours. We therefore used ALMA in Cycle 0 to observe a large sample of submillimeter galaxies in the Extended Chandra Deep Field South (ECDFS), a 30 × 30 field with deep, multi-wavelength coverage from the radio to the X-ray (Giacconi et al 2001;Giavalisco et al 2004;Lehmer et al 2005;Beckwith et al 2006;Luo et al 2008;Miller et al 2008;Weiß et al 2009;Devlin et al 2009;Scott et al 2010;Ivison et al 2010a;Miller et al 2013). The 126 submillimeter sources we target were previously detected in the LABOCA ECDFS Submillimeter Survey (LESS; Weiß et al 2009), the largest, most homogenous, and most sensitive blind 870 μm survey to date.…”
Section: Introductionmentioning
confidence: 99%
“…The AzTEC/ASTE GOODS-S observations reported a 1σ depth of about 0.48−0.73 mJy beam −1 , which is below the estimated confusion background limit of 2 mJy beam −1 (Scott et al 2010). The confusion background is the sea of faint unresolved sources in the sky, creating an extended emission that can potentially bias detections below the confusion background limit (Hogg 2001).…”
Section: Inference Of Astrophysical Informationmentioning
confidence: 96%
“…For that, we revisit the AzTEC/ASTE GOODS-S survey, which is considered to be a blank field. For that reason, this survey has been extensively studied and used as a trial data set for extensions to the AzTEC pipeline (Scott et al 2010;Scott et al 2012;Downes et al 2012;Yun et al 2012). Although astrophysical foregrounds are not expected, these observations were certainly contaminated by bright atmospheric foregrounds.…”
Section: Inference Of Astrophysical Informationmentioning
confidence: 99%